Entrepreneurial basic capital and its contribution to developing multicultural islamic education - Mariyono, Dwi; Maskuri, Maskuri; Ghony, Muhammad Djunaidi (Journal of Education and Learning (EduLearn), 2025)
This research aims to explore the role of entrepreneurial spirit in the development of multicultural Islamic education at Bahrul Maghfiroh Islamic Boarding School in Malang. Using a qualitative approach with the ethnographic case study method. The research questions are: i) what entrepreneurial spirit is used as capital in developing multicultural Islamic education at Bahrul Maghfiroh Islamic Boarding School in Malang? and ii) how does the entrepreneurial spirit contribute to the development of multicultural Islamic education at Bahrul Maghfiroh Islamic Boarding School in Malang? data and data sources were obtained through interviews, observations, and documents. This study found that the spirit of entrepreneurship plays an important role in developing multicultural Islamic education in pesantren. Capital in entrepreneurship is not always synonymous with tangible things such as money and gold. The contribution of the entrepreneurial spirit is very real and significant because it helps create an inclusive and conducive learning environment and encourages the growth of creativity and innovation among students. In addition, social entrepreneurship in the pesantren environment can also grow and develop synergistically to improve people's lives.